Clothes call - change it. don't bin it - Ang, Anna Hui Yu (2015)
Clothes Call is the first local studentled campaign promoting clothes repurposing the recycling, and the reusing of unwanted clothes through modification. Led by four final year students of the Wee Kim Wee School of Communication and Information at the Nanyang Technological University, Clothes Call is a groundup movement driving the act of clothes repurposing as an alternative to disposal. Clothes Call targets Singaporean youths aged 15 to 35, activating them to be environmentally conscious when handling their unwanted clothes, to explore options of repurposing before disposal. By informing them about the benefits of clothes repurposing and demonstrating that clothes repurposing is a lifestyle choice, Clothes Call aims to make clothes repurposing a new interest among the public and media. Through these, the campaign aims to bring attention to textile wastes, an uncommon recyclable among youths, strengthening Singapore’s efforts to encourage an environmentally responsible people. This report delves into the findings and analyses of the primary and secondary research, which form the fundamental basis of the campaign’s rationale, strategies and tactics. It also details the campaign process, from conceptualisation to implementation. This report then evaluates the overall performance of the campaign, discussing the effectiveness, challenges, and limitations to discover future directions for the longevity of this movement. The last section of the report is an extensive appendix comprising materials that complement the main text, providing a detailed background to the campaign process.